SUPPORTIVE WORK ENVIRONMENT AND TURNOVER INTENTION: TESTING THE MEDIATION EFFECT OF PERSON-ORGANIZATION FIT - Noor Azlina Yusoff; Yusliza Mohd Yusoff (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2022)
The study’s overarching goal was to experimentally investigate how Person-Organization Fit (POF) mediates the connection between a Supportive Work Environment (SWE) and an employee Turnover Intention (TI). Academic staff from Malaysian Research Universities (RUs) were be selected using a technique of convenience sampling. Multiple items from previous studies were incorporated into questionnaires to collect responses utilizing quantitative methods. Partial Least Squares (PLS) Structural Equation Modelling (SEM) were performed using the Smart PLS 3.2.8 software sampling technique for statistical analysis and testing the proposed hypothesis. The results of this study are meant to demonstrate why SWE is linked favourably and significantly to TI. Furthermore, POF worked as a mediator between an SWE and TI relationship. This study finds that university management should continue developing ways to deliver SWE to establish a healthy environment for employees, which would lessen their willingness to resign. The literature connecting SWE and TI will benefit significantly from this research while stressing the essential retention aspects that must be considered. Additionally, the study explains the constraints and scope of future research.